SISTEM PENGAMBIL KEPUTUSAN PENERIMA BEASISWA BBM DAN PPA MENGGUNAKAN ANALIYTICAL HIERARCHY PROCESS - F.X. Wisnu Yudo Untoro; Nuroh Istighfarin Hariyani; Arvin Claudy Frobenius (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
One of the tasks of the student affairs department at tertiary institutions is to select prospective students who receive the BBM and PPA scholarships. Each prospective scholarship recipient must receive one of the types of scholarships offered and are not allowed to receive both types of BBM and PPA scholarships. Taking into account the requirements and criteria that apply to the BBM and PPA scholarships there are differences and there are quite a number of candidates who submit them, of course the time needed to make a decision on scholarship recipients manually will be long. Therefore, it is proposed that a decision making algorithm for BBM and PPA scholarship recipients uses the concept of an analytical hierarchy process that is able to make judgments based on the criteria that exist in each individual. The proposed algorithm is implemented using PHP programming by storing both the input data and the results of data processing in the MySQL database. The experimental results show that the decision-making algorithms for BBM scholarship recipients and PPA scholarship recipients produce decisions that are as expected and can be used as decision makers that are free from acts of collusion, corruption, nepotism, and abuse of authority.